Safety and feasibility of upper limb vascular access for cardiac catheterization in anticoagulated and non-anticoagulated patients. Issue 6 (November 2021) - Marques, Felipe Pereira Lima; Valle, Felipe Homem; Araujo, Gustavo Neves de; Pinheiro Machado, Guilherme; Amantea, Rodrigo; Fuchs, Felipe C; Bergoli, Luiz Carlos; Goncalves, Sandro Cadaval; Wainstein, Marco; Wainstein, Rodrigo
Background: The upper limb approach utilizing transradial access for combined left and right heart catheterization (CLRHC) and ultrasound-guided antecubital venous access for isolated right heart catheterization (IRHC) are strategies that may reduce risks, especially in anticoagulated patients. combined left and right heart catheterization Objectives: To assess safety and feasibility of upper limb approach for IRHC or CLRHC in anticoagulated versus non-anticoagulated patients. Methods: Ninety-three patients who underwent IRHC or CLRHC with ultrasound-guided antecubital venous access and transradial arterial access were prospectively enrolled. The primary outcome was a composite of procedure failure and incidence of immediate vascular complications. Results: Of the 93 patients, 44 (47%) were on anticoagulation and 49 (53%) were not. Mean age was 54 ± 17 and 53 ± 15 years, respectively. Atrial fibrillation (39% vs 15%) and chronic kidney disease (21% vs 6%) were more common in anticoagulated patients. The main indication for anticoagulation was deep vein thrombosis/pulmonary thromboembolism in 22 patients (50%). The primary outcome occurred in 4 (8%) patients in the non-anticoagulated group as compared with 0 in the anticoagulated group ( p = 0.12). Procedure failure occurred in two patients (4%) and immediate vascular complications in two patients (4%) in the non-anticoagulated group ( p = 0.3 for all). There was no difference between groups regarding duration of the procedure, radiation dose, fluoroscopy time, post-procedure recovery room time and median time to venous or arterial hemostasis. Conclusions: The upper limb approach for heart catheterization had similar rates of procedure failure and immediate vascular complications in anticoagulated patients when compared to non-anticoagulated patients.